Investor Sentiment Aligned: A Powerful Predictor of Stock Returns - Huang, Dashan; Jiang, Fuwei; Tu, Jun; Zhou, Guofu (Review of Financial Studies, 2015)
We propose a new investor sentiment index that is aligned with the purpose of predicting the aggregate stock market. By eliminating a common noise component in sentiment proxies, the new index has much greater predictive power than existing sentiment indices have both in and out of sample, and the predictability becomes both statistically and economically significant. In addition, it outperforms well-recognized macroeconomic variables and can also predict cross-sectional stock returns sorted by industry, size, value, and momentum. The driving force of the predictive power appears to stem from investors' biased beliefs about future cash flows.